Our experience of diagnostic laparoscopy in chronic abdominal pain - Rajiv B. Jadhav; Vijay (Al Ameen Medical College, 2018)
Background: In patients with chronic abdominal pain, laparoscopy can identify abnormal findings and improve the outcome in a majority of patients with chronic abdominal pain, as it allows surgeon to see and treat many abdominal conditions that cannot be diagnosed otherwise. However, the role of laparoscopy in chronic abdominal pain is still debated by some authors who deny its value in adhesiolysis. We are presenting our experience regarding diagnostic laparoscopy in chronic abdominal pain. Methods: All patients undergoing laparoscopy for chronic abdominal pain were included in the study from Jan 2013 to Sept 2014. The pain in all patients was of unknown etiology despite all the investigative procedures. Outcome measured included the overall efficacy of diagnostic laparoscopy in finding a cause of chronic abdominal pain, diagnosis made and response to pain. Results: A total of 100 patients (68 women and 32 men) with an average age of 31.6yrs underwent diagnostic laparoscopy for the evaluation and treatment of chronic abdominal pain. Findings included chronic appendicitis in 68, adhesions in 12, abdominal koch's in 10, cholecystitis in 4, cirrhosis in 4, ovarian cyst in 4, fimbrial cyst in 4 and 14 patients had no obvious pathology. 90% of patients had pain relief at the time of follow up. Conclusion: Laparoscopy is a safe, quick and effective modality of investigation, therapeutic intervention can be done at the same sitting. Diagnostic laparoscopy has a high diagnostic and therapeutic efficiency.